Antioxidant Effects of PS5, a Peptidomimetic of Suppressor of Cytokine Signaling 1, in Experimental Atherosclerosis - Sara La Manna; Laura Lopez-Sanz; Susana Bernal; Luna Jimenez-Castilla; Ignacio Prieto; Giancarlo Morelli; Carmen Gomez-Guerrero; Daniela Marasco (MDPI AG, 2020)
The chronic activation of the Janus kinase/signal transducer and activator of the transcription (JAK/STAT) pathway is linked to oxidative stress, inflammation and cell proliferation. Suppressors of cytokine signaling (SOCS) proteins negatively regulate the JAK/STAT, and SOCS1 possesses a small kinase inhibitory region (KIR) involved in the inhibition of JAK kinases. Several studies showed that KIR-SOCS1 mimetics can be considered valuable therapeutics in several disorders (e.g., diabetes, neurological disorders and atherosclerosis). Herein, we investigated the antioxidant and atheroprotective effects of PS5, a peptidomimetic of KIR-SOCS1, both in vitro (vascular smooth muscle cells and macrophages) and in vivo (atherosclerosis mouse model) by analyzing gene expression, intracellular O2•− production and atheroma plaque progression and composition. PS5 was revealed to be able to attenuate NADPH oxidase (NOX1 and NOX4) and pro-inflammatory gene expression, to upregulate antioxidant genes and to reduce atheroma plaque size, lipid content and monocyte/macrophage accumulation. These findings confirm that KIR-SOCS1-based drugs could be excellent antioxidant agents to contrast atherosclerosis.